Reforming Hudud ordinances to reconcile Islamic criminal law with international human rights law - Gabriel, Mark A (Department of Public Law, 2017)
International human rights laws are grossly violated by the hudud ordinances, with their extremely cruel punishments, including stoning for adultery, beheading for apostasy, and amputation for theft. Pakistan, Sudan, Brunei Darussalam and Saudi Arabia, for example, follow the doctrines of the four main Sunni schools of jurisprudence and enforce hudud ordinances, thereby violating some of the core international human rights law instruments to which they are State Parties. Orthodox Muslims generally defend the hudud ordinances, claiming that they are divine and immutable. This study refutes the aforementioned claim and demonstrates that it is legitimate and possible to reform hudud punishments to reconcile them with international human rights law. The thesis differentiates between Shariah and Islamic law. It argues that Shariah refers to the divine rulings recorded in the Qur'an and correct Sunnah, while Islamic law is not fully divine, for it includes also such prescriptions that have been developed by the human effort of Islamic jurists. The thesis demonstrates that reformation is an Islamic concept that requires that Muslims read the teachings of the Qur'an and the Sunnah in the context of their own time and environment. It is postulated, therefore, that the rulings of Islamic law need to be examined in the light of the Qur'an, the correct Sunnah and the Islamic core values promoted in them. These include several internationally protected human rights, such as the right to life, equality, and freedom of religion. The thesis points out that the main purpose of Shariah is to serve the benefit of the people and to protect them from harm. To this end, Shariah has provided the Islamic principles of reality and necessity. These require that the reality of life and the needs of the people be considered at all times. If necessary for the sake of the people, the principles allow for exceptions to be made to even definite provisions. It, further, demonstrates how these principles can be applied to reform the hudud ordinances to reconcile them with international human rights law.